Influence of the Processes of Fluffing the Flax Stem Strips on the Structural Parameters of the Layer - Alexander N. Zintsov; Mixail M. Kovalev; Gennady A. Perov; Mixail G. Perov; Vyacheslav A. Dobretsov (Инженерные технологии и системы, 2023)
Introduction. The efficiency of separating long flax fiber from the flax straw largely depends on the structural parameters of the layer of flax stems. Modern fluffers for flax strips create random distortions and intersection of the layer of flax stems under the pick-up drum. These disadvantages of existing machines are minimized in an experimental fluffer, in which a layer of flax stems moves over the pick-up drum with a kinematic mode indicator equal to one. Aim of the Article. The study is aimed at finding means and methods for preserving the structural parameters of the layer of flax stems when fluffing flax straw strips. Materials and Methods. Experimental studies were carried out according to existing and newly developed methods, and the analysis of flax fiber was carried out according to the current GOST standards. The experiments were carried out on the flax strips formed by the LC-4A flax harvester. After grass sprouted through the strips of flax stems, they were fluffed with the serial machine VL-3 and an experimental fluffer. For each variant, the necessary measurements of the main structural parameters of the stem strip and collection of samples for analysis were made before the unit passed and after fluffering the flax stem strip. The results of measurements and processing of samples were processed using the methods of mathematical statistics. Results. It was found that macro-bends of the original and processed flax strips were in all the experiments. At the same time, the range of changes in the curvature of the flax strip outside the cutoff frequencies expanded 2.3 times under the influence of the working tools of the serial tedder VL-3. The randomness of these pulsations was caused by an increase in the distortion and elongation of the flax stems in the strip by 6.0° and 6.9%, respectively. At the same time, the experimental fluffer produced the smallest changes in the structural parameters of the flax stem layer. The technological evaluation of the flax straw confirmed the advantages of the experimental fluffer in comparison with the serial VL-3, which has an average production of long fiber higher by 0.65% and 0.5 units of number. Discussion and Conclusion. The analysis of the obtained results indicates the practicability of fluffing flax strips by picking up and moving the stems from above the pick-up drum with its kinematic mode index equal to one.